Improving energy efficiency of bipedal walking using nonlinear compliant mechanisms. Issue 1 (14th December 2021) - Luo, Yinnan; Zirkel, Marten; Römer, Ulrich J.; Zentner, Lena; Fidlin, Alexander
Abstract: A method to improve the energy efficiency of a bipedal robot by coupling its thighs with compliant smart mechanisms is introduced. The walking gaits are driven by electric motors in its revolute joints, whose reference trajectories are generated via numerical optimization. The optimized nonlinear characteristic of the compliant mechanism modifies the free oscillation frequency of the system that matches the current double step frequency even under different conditions, which results in a very high energy efficiency.